2014
DOI: 10.1017/s1041610213002445
|View full text |Cite
|
Sign up to set email alerts
|

Worry about performance: a unique dimension of caregiver burden

Abstract: Our results corroborate earlier studies that WaP is a distinct burden dimension not correspondent with traditional ZBI domains. WaP is germane to many Asian societies where obligation values to care for family members are strongly influential. Further studies are needed to better delineate the construct of WaP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 30 publications
(62 reference statements)
3
49
2
1
Order By: Relevance
“…Previous research in Asian countries reported that traditional Japanese families have rules that govern an individual's perceptions of duty, obligation, and responsibility and that in both Chinese and Japanese cultures, caregiver burden is influenced by those cultural constructs . Another study reported that caregiver obligation values may have a greater effect than family caregiving in Asian countries . We thought that these differences between Western countries and Asian family norms would lead to a difference in caregiving appraisal.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous research in Asian countries reported that traditional Japanese families have rules that govern an individual's perceptions of duty, obligation, and responsibility and that in both Chinese and Japanese cultures, caregiver burden is influenced by those cultural constructs . Another study reported that caregiver obligation values may have a greater effect than family caregiving in Asian countries . We thought that these differences between Western countries and Asian family norms would lead to a difference in caregiving appraisal.…”
Section: Discussionmentioning
confidence: 80%
“…35 Another study reported that caregiver obligation values may have a greater effect than family caregiving in Asian countries. 36,37 We thought that these differences between Western countries and Asian family norms would lead to a difference in caregiving appraisal. Our results suggest that Japanese family caregivers, and perhaps also caregivers from other Asian countries and even Japanese-American family caregivers, require particular support to help decrease their personal strain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies corroborate the existence of WaP as a distinct dimension of burden among adult children caregivers, which may be particularly salient in Asian societies that are often heavily influenced by notions of filial piety and obligatory care (Cheah et al, 2012). Unlike role and personal strain, WaP is poorly correlated with other factor scores, significantly endorsed even in milder stages of cognitive impairment and is not predicted by "conventional" factors such as functional impairment and behavioral problems (Lim et al, 2014). In support of this, a recent confirmatory factor analysis revealed that ZBI factor models premised on the three key dimensions of role strain, personal strain, and WaP were superior to one-factor (total score) and two-factor (role/personal strain) models (Li et al, 2018).…”
mentioning
confidence: 80%
“…patients with dementia) also appeared to be influenced by notions of filial piety and obligatory care. A study investigating the factor structure of the Zarit Burden Interview among Singaporean caregivers of dementia patients identified a unique dimension described as 'worry about caregiver performance', (22) suggesting the presence of expectations for the standard of care provided among Asian caregivers. In Malaysia, a country that is culturally similar to Singapore, it was found that having formal support in caregiving (such as having a domestic maid or a private nurse) did not alleviate the burden of family caregivers who were caring for dementia patients, emphasising the value of providing familial care.…”
Section: Discussionmentioning
confidence: 99%